Creating Transformative Spaces in Education: Facing Humanity, Facing Violence - Todd, Sharon (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2015)
This paper considers the difficulties that accompany projects in education variously configured around a multicultural or intercultural label, particularly when they are built upon, for example, idealised conceptions of humanity, notions of the common good and dialogue, or ideas of recognition.  My premise here is that, while such idealisations may be constructed with the best of intentions, they occlude discussions of how to face the violent realities that can also be part of social interaction. My focus here is on the existential conditions that frame our encounters with other people, and how such existential concerns lead us to confront more openly the violence that can inhere in such encounters. Beginning from this existential position, I argue, actually invites alternative ways of formulating transformative work in education, namely a focus on the present. Secondly, I turn to explore the transformative spaces created by performance artist Marina Abramovic, and how her projects reveal what we are up against existentially when it comes to facing humanity in the here and now, in all its messiness. And, finally, I make the suggestion that an education committed to the existential conditions of facing humanity can be built on a reconceptualization of conversation, as opposed to dialogue. Here I argue that conversation offers the kind of potential for transformation in its open-endedness and anarchic sensibilities.